SOIL CHARACTERISTICS AND SUBSTATION EARTHING IN BAYELSA STATE - Afa, John Tarilanyo; Ngobia, Felix Opuama (European Scientific Journal, ESJ, 2013)
From previous investigations of soil resistivity in Bayelsa State, the soil was found to be corrosive in most part of the state. Substation which is the most sensitive part of power transmission and distribution system requires effective and safe earthing systems. A study was carried out in the three main soil divisions. The resistivity of the soil was tested at the depths of 0.5m, 0.8m, 1.2m and 1.5meters. The pH values of the soil in the area at a depth of 1.0meters were tested in the laboratory. The tests showed that the soil resistivity at a depth below 1.2meters was below 20Î©-m in the coastal site, the average pH value was about 5.8. The results of resistivities confirmed that the soil is corrosive and the value is within the corrosive soil given in all available technical literatures. From the performance of the graph of soil resistivity, the soil maintains a permanent moisture level at 1.5meters. The soil condition offers an effective fault current dissipation but is prone to corrosion effect. For effective earthing system and for durability solid copper grid was recommended because copper is not affected by corrosion in most corrosive soil and is thermodynamically stable.